Laws That Bit The Bullet: A Review of Legislative Responses to School Shootings - Schildkraut, Jaclyn (American journal of criminal justice, 2014)
The recent mass shooting at Sandy Hook Elementary School in Newtown, Connecticut sparked an immediate discourse calling for a review of gun control legislation. However, this discourse was not new; rather, it was one that routinely follows this type of tragedy. In the wake of school shootings such as Columbine, Virginia Tech, and Jonesboro, a similar discourse appeared which prompted policymakers to introduce a number of pieces of legislation aimed at more efficient firearms regulation. While a few of these bills were enacted, many never made it past introduction. The flurry of legislative responses to such incidences warrants further discussion as to whether these bills are effective, or rather simply “feel good legislation.” Further, public opinion is a driving force behind such policy, but how can this change in the wake of school shootings? This paper examines both considerations and proposes directions for continued research in this critical and understudied area.